2002
DOI: 10.1021/np010579u
|View full text |Cite
|
Sign up to set email alerts
|

Mammea Coumarins from the Flowers of Mammea siamensis

Abstract: Four new mammea coumarins, mammea E/BA cyclo D (1), mammea E/BC cyclo D (2), mammea E/BD cyclo D (3), and mammea E/AC cyclo D (4), were isolated from the flowers of Mammea siamensis, along with six known coumarins. Extensive 1D and 2D NMR experiments and other spectroscopic studies, as well as chemical transformations, were employed to determine the structures of 1-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…[1][2][3][4] They show diverse biological and pharmacological activities ranging from antimicrobial, anti-arrhythmic, antitumor, antifungal, anti-HIV, anti-osteoporosis to anti-inflammatory. [5][6][7][8][9][10][11][12] Apart from their pharmaceutical applications, [13][14] coumarins have been used as additives in foods, perfumes and cosmetics as well as in the preparation of optical brighteners, laser dyes, fluorescent labels and nonlinear optical chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] They show diverse biological and pharmacological activities ranging from antimicrobial, anti-arrhythmic, antitumor, antifungal, anti-HIV, anti-osteoporosis to anti-inflammatory. [5][6][7][8][9][10][11][12] Apart from their pharmaceutical applications, [13][14] coumarins have been used as additives in foods, perfumes and cosmetics as well as in the preparation of optical brighteners, laser dyes, fluorescent labels and nonlinear optical chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers of this plant have been used for preparing a heart tonic in Thai traditional medicine ("Sarapi" in Thai). [1][2][3][4][5][6][7][8][9][10] Several coumarins, [1][2][3][4][5][6][7] xanthones, 8,9) triterpenoids, 10) and steroids 10) have been isolated from the flowers, 1,2,6,7,10) seeds, 3,9) twigs, 4,8) and bark 5) of this plant. In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells.…”
mentioning
confidence: 99%
“…Fr. OSE3 (460 mg) was separated using CC (silica gel, 0-25% EtOAc-petroleum ether) and then RP 18 (MeOH-H 2 O) and finally GPC to yield 1,6,7-trihydroxyxanthone (7, 12.0 mg), 1,3,7-trihydroxyxanthone (8,6.0 mg) and 1,7-dihydroxy-3-methoxyxanthone (9, 5.0 mg).…”
Section: Methodsmentioning
confidence: 99%
“…3) Earlier studies have shown that the genus is a rich source of coumarins and xanthones, some of which have potential pharmacological and therapeutic properties. [4][5][6][7][8][9] We here report the chemical constituents of the bark of Mammea siamensis collected in south Vietnam with the isolation of a new and four known coumarins as well as seven xanthones. In addition, new data on the anti-proliferative activity of the coumarins surangins C-D and theraphins B-C and their methylated derivatives were generated using sulforhodamine B (SRB) assay on four human cancer cell lines, MCF-7 (breast adenocarcinoma), HeLa, DLD-1 (colon cancer) and NCI-H460 (human lung cancer).…”
Section: Regular Articlementioning
confidence: 95%